High-fat diets enhance and delay ursodeoxycholic acid absorption but elevate circulating hydrophobic bile salts - Huang, Liang; Wei, Wei; Huang, Xiaomei; Li, Xuejing; Liu, Haisha; Gui, Lanlan; Jiang, Jinping; Wan, Linfei; Zhou, Xiangxiang; Ding, Jingsong; Jiang, Xuehua; Zhang, Bikui; et al. (Frontiers in Pharmacology, 2023)
Background: Ursodeoxycholic acid (UDCA) is a natural drugmedicine essentially for the treatment of cholestatic liver diseases. The food effects on the absorption of UDCA and the disposition of circulating bile salts remain unclear despite of its widespread global uses. This study aims to investigate the effects of high fat (HF) diets on the pharmacokinetics of UDCA and disclose how the circulated bile salts were simultaneously perturbed. Methods: After an overnight fast, a cohort of 36 healthy subjects received single oral dose (500mg) of UDCA capsules, and another cohort of 31 healthy subjects received the same dose after consuming a 900 kcal HF meal. Blood samples were collected from 48 hours pre-dose up to 72 hours post-dose for pharmacokinetic assessment and bile acid profiling analysis. Results: The HF diets significantly delayed the absorption of UDCA, with the Tmax of UDCA and its major metabolite, glycoursodeoxycholic acid (GUDCA), changed from 3.3 h and 8.0 h in the fasting study to 4.5 h and 10.0 h in the fed study, respectively. The HF diets did not alter the Cmax of UDCA and GUDCA but immediately led to a sharp increase of the plasma levels of endogenous bile salts including those hydrophobic ones. The AUC0-72h of UDCA significantly increased from 25.4 µg.h/mL in the fasting study to 30.8 µg.h/mL in the fed study, while the AUC0-72hexposure of GUDCA showed no differenceremained consistent in both studies. As a result, the Cmax of total UDCA (the sum of UDCA, GUDCA and TUDCA) showed a significant elevation while the AUC0-72h of total UDCA showed a slight increase without significance in the fed study compared to the fasting study. Conclusion: The HF diets delay UDCA absorption due to the extension of gastric empty time. Although UDCA absorption was slightly enhanced by the HF diets, the beneficial effect may be limited in consideration of the simultaneous elevation of circulating hydrophobic bile salts.